Risk disclosure in prodromal Parkinson's disease – A survey of neurologists. (January 2023) - Kayis, Gorkem; Yilmaz, Rezzak; Arda, Berna; Akbostancı, M. Cenk
Abstract: Introduction: In the absence of a disease-modifying treatment and prognostic uncertainty, ethics of risk disclosure in prodromal Parkinson's disease (PD) is challenging. Previous studies highlighted several facets of these challenges from the perspective of involved parties. However, to date, the view of neurologists who may encounter individuals with prodromal PD remained unrepresented. Moreover, cross-cultural differences intrinsic to the ethics of risk disclosure are yet to be elucidated. Therefore, we investigated the attitude of neurologists toward risk disclosure in prodromal PD. Methods: In this observational study, Turkish neurologists were invited to fill out a questionnaire evaluating their stance on risk disclosure regarding an individual with polysomnography-confirmed REM sleep behavior disorder, which is the strongest risk factor for PD. Results: More than 90% of the participating 222 neurologists were familiar with prodromal PD. While 15.3% stated that the risk should be disclosed in any case, 6.8% chose no disclosure. The remaining 77.9% favored disclosure only under certain circumstances, the plurality of which was the individual's consent to know about the risk. After reminding the potential neuroprotective effects of exercise and diet, neurologists who chose the option of "no disclosure" decreased to 3.2% (McNemar's test p = 0.008). No significant differences among the neurologists were found regarding sex, academic title, or field of interest. Conclusion: The majority of the neurologists found it appropriate to disclose the risk of future PD only if the individual expresses a desire to know. Also, recognition of the impact of lifestyle factors on PD is important in prognostic counseling. Highlights: Ethics of risk disclosure in prodromal Parkinson's disease is a matter of debate. Neurologists believe detecting Parkinson's at the prodromal stage is necessary. Neurologists favored disclosure, provided that the individual requests it. Mentioning the effects of diet and exercise altered views toward risk disclosure.